Pengembangan Sistem Validasi Dokumen Pasca Perceraian Menggunakan Optical Character Recognition dan Relationship-Based Access Control - Erik Rahman; Resmi Darni; Dony Novaliendry; Vikri Aulia (Universitas Merdeka Malang, 2026)
This study aims to address the problem of post-divorce population document validation, which is still carried out manually and is prone to errors and delays. The proposed approach is the development of a document validation system using Optical Character Recognition (OCR) for data extraction and Relationship-Based Access Control (ReBAC) for relationship-based access management. The research dataset consisted of 122 identity documents in JPG, PNG, and PDF formats that had undergone anonymization and preprocessing stages, including grayscale conversion and noise removal. The testing results showed that the OCR system achieved matching rates of 74.59% for the National Identification Number (NIK) attribute, 89.34% for the name attribute, and 75.41% for the address attribute, with an average match score of 84.65%. In addition, ReBAC testing demonstrated a 100% success rate across 32 testing scenarios in preventing unauthorized access based on inter-entity relationships. These results indicate that the developed system is capable of improving efficiency, accuracy, and security in the post-divorce population document validation process.